2023
DOI: 10.3390/foods12030552
|View full text |Cite
|
Sign up to set email alerts
|

Natural Killers: Opportunities and Challenges for the Use of Bacteriophages in Microbial Food Safety from the One Health Perspective

Abstract: Ingestion of food or water contaminated with pathogenic bacteria may cause serious diseases. The One Health approach may help to ensure food safety by anticipating, preventing, detecting, and controlling diseases that spread between animals, humans, and the environment. This concept pays special attention to the increasing spread and dissemination of antibiotic-resistant bacteria, which are considered one of the most important environment-related human and animal health hazards. In this context, the developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 152 publications
0
8
0
2
Order By: Relevance
“…The study yielded positive outcomes, including the evaluation of bacteriophage infectivity against Vibrio strains and the successful protection of shrimp against Acute Hepatopancreatic Necrosis Disease (AHPND) and bacterial challenges [ 91 ]. Field trials involving the use of cultured bacteriophages and non-pathogenic Vibrio demonstrated improved protection against infections, with minimal observed mortality during the adaptive research phase [ 92 ]. Morphological tests conducted on the shrimp indicated their overall health and well-being, as no abnormal deformities were detected.…”
Section: Discussionmentioning
confidence: 99%
“…The study yielded positive outcomes, including the evaluation of bacteriophage infectivity against Vibrio strains and the successful protection of shrimp against Acute Hepatopancreatic Necrosis Disease (AHPND) and bacterial challenges [ 91 ]. Field trials involving the use of cultured bacteriophages and non-pathogenic Vibrio demonstrated improved protection against infections, with minimal observed mortality during the adaptive research phase [ 92 ]. Morphological tests conducted on the shrimp indicated their overall health and well-being, as no abnormal deformities were detected.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have demonstrated the effectiveness of Salmonella phages in reducing Salmonella levels within the poultry industry. These investigations have revealed significant reductions in Salmonella colonization in the gastrointestinal tract of chickens, while simultaneously ensuring their health and well-being ( Lavilla et al, 2023 ). Additionally, research has explored the use of phages as a disinfectant to eliminate Salmonella from poultry drinkers, a critical point for Salmonella cross-infection ( Korzeniowski et al, 2022 ), as well as from cement floors where Salmonella exhibits high resistance to conventional disinfection methods ( Sevilla-Navarro et al, 2020a ).…”
Section: Discussionmentioning
confidence: 99%
“…The use of phages has already been explored in some areas related to food, as a therapeutic agent, where phages are used to reduce pathogen colonization in living animals during primary production before slaughtering and also for sanitation purposes to disinfect food contact surfaces and equipment [ 48 ].…”
Section: Phagesmentioning
confidence: 99%